2015
DOI: 10.1152/jn.00059.2015
|View full text |Cite
|
Sign up to set email alerts
|

Bracing of the trunk and neck has a differential effect on head control during gait

Abstract: During gait, the trunk and neck are believed to play an important role in dissipating the transmission of forces from the ground to the head. This attenuation process is important to ensure head control is maintained. The aim of the present study was to assess the impact of externally restricting the motion of the trunk and/or neck segments on acceleration patterns of the upper body and head and related trunk muscle activity. Twelve healthy adults performed three walking trials on a flat, straight 65-m walkway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 53 publications
1
7
0
Order By: Relevance
“…31 Further, older adults (especially those with an increased fear of falling) demonstrate a stronger coupling between the trunk and head, 27 revealing an increase in trunk stiffness associated with a more cautious gait strategy. 32 While measures of gait from the current study and previous literature report gait variables are similar to healthy controls, a fear of re-injury may elicit similar alterations in coordination strategies to those seen in older adults. The current study revealed in the KOOS results that the ACLR group still experience pain, reduced function in sport and recreation, as well as a reduced knee-related quality of life.…”
Section: Slowing Of Postural Reaction Time With Aclrsupporting
confidence: 59%
“…31 Further, older adults (especially those with an increased fear of falling) demonstrate a stronger coupling between the trunk and head, 27 revealing an increase in trunk stiffness associated with a more cautious gait strategy. 32 While measures of gait from the current study and previous literature report gait variables are similar to healthy controls, a fear of re-injury may elicit similar alterations in coordination strategies to those seen in older adults. The current study revealed in the KOOS results that the ACLR group still experience pain, reduced function in sport and recreation, as well as a reduced knee-related quality of life.…”
Section: Slowing Of Postural Reaction Time With Aclrsupporting
confidence: 59%
“…Our current findings show that the head pitch accelerations are greater than the sled acceleration almost in all subject conditions. We think that constraining the trunk may have impeded the ability of the trunk and neck to attenuate the momentum from the sled, ultimately increasing the amplitude and complexity of head acceleration ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…In gait analysis, the focus so far has been on the actions of the lower extremities. The contribution of the trunk and neck has also been considered, as well as of the shoulder girdle and upper extremities [ 12 , 13 ]. However, a special involvement of the trunk and upper extremities [ 14 ] has been mentioned for various neurological diseases [ 15 ], of which some are still associated with their first describers, such as the neurologists Duchenne de Boulogne and Wernicke or the surgeon Friedrich Trendelenburg.…”
Section: Methodsmentioning
confidence: 99%